Prospective study on the clinico-hematological profile of dengue fever patients in Navi Mumbai - Sankhe, Prachi; Jadhav, Priyanka; Meduri, Praveen (International Journal of Advances in Medicine, 2021)
Background: It has been seen that epidemiology and clinical presentation of dengue infection differs significantly across geographical areas. The present study was done to study clinico-hematological profile of patients with dengue fever in Navi Mumbai, Maharashtra. Methods: This prospective observational study was conducted at a tertiary level teaching hospital in Navi Mumbai. All patients were observed over their entire duration of their hospital stay (up to 7 days). We included adult patients of both gender (males or females) who were admitted with clinically and serological diagnosed dengue fever, consenting to participate in the study. The clinical, laboratory and radiological findings of the patients were noted. Results: All 80 patients presented with fever while 71.25% had myalgia. Retro-orbital pain, rash and vomiting was observed in 38%, 26% and 26% respectively, whereas 23.75% patients were having cough and bleeding from any site. Three fourths of the patients were diagnosed with dengue, 18.75% and 6.25% were diagnosed with DHF and DSS. respectively. Hepatosplenomegaly was increasing from day 1 (9%) to 6th (60%) and 7th (60%) day. Mean haemoglobin levels and haematocrit started increasing from second day onwards, while WBC count and platelet count increased gradually from first day onwards. Splenomegaly was diagnosed in 3.75% of patients while hepatosplenomegaly and fatty liver was observed in 8.75% and 2.5% respectively. There were two deaths, both were cases of DSS. Conclusions: Almost all the patients included in our study showed both haematological and biochemical abnormalities.